2011
DOI: 10.1523/jneurosci.4960-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Function in Healthy Carriers of theCLUAlzheimer's Disease Risk Variant

Abstract: Alzheimer's disease is a devastating, common, progressive dementia with considerable heritability. Recently, a genetic variant associated with the disease was discovered at CLU (rs11136000) with genome-wide support. Here we show, using an imaging genetics approach in a large genotyped sample, that healthy carriers of the variant exhibit altered coupling between hippocampus and prefrontal cortex during memory processing, mirroring clinical evidence of disturbed connectivity in patients and providing a neurogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…It has been suggested that memory breakdown during AD is associated with a marked reduction in integrated activity within a distributed network that includes the hippocampus and DLPFC (Grady et al, 2001). Moreover, fMRI studies have also provided evidence for significantly reduced coupling between the hippocampus and DLPFC during episodic memory retrieval (Erk et al, 2011), as well as aberrant activation in the same regions, during WM performance in healthy young individuals carrying the CLU risk allele (C allele of 11136000) for AD (Lancaster et al, 2011). Although they are in a different cognitive domain, these results additionally emphasize the relevance of hippocampal-prefrontal interaction to the pathology of AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that memory breakdown during AD is associated with a marked reduction in integrated activity within a distributed network that includes the hippocampus and DLPFC (Grady et al, 2001). Moreover, fMRI studies have also provided evidence for significantly reduced coupling between the hippocampus and DLPFC during episodic memory retrieval (Erk et al, 2011), as well as aberrant activation in the same regions, during WM performance in healthy young individuals carrying the CLU risk allele (C allele of 11136000) for AD (Lancaster et al, 2011). Although they are in a different cognitive domain, these results additionally emphasize the relevance of hippocampal-prefrontal interaction to the pathology of AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in task-related activation (as a general neuroimaging phenotype for AD susceptibility) could reflect a dysregulation of neurovascular coupling [40] or exaggerated calcium signaling [41][42][43], although these hypotheses would need to be formally tested. Increased activation could also reflect a compensatory neural response due to incipient changes in brain macro/microstructure [24] and/or functional connectivity [21,44] that have previously been associated with the rs11136000 C risk allele.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that carriers of the CC risk genotype have increased activation in a working memory (WM)-elated network, which may reflect compensatory activation in response to increasing task complexity [20]. Another study suggested that the CLU variant may modulate functional connectivity between memory regions (right dorsolateral prefrontal cortex and right hippocampus) during episodic memory recall and recognition [21]. The CLU variant may also affect neural activity during attention [22] and resting-state alpha-rhythm activity in older healthy subjects [23].…”
Section: Introductionmentioning
confidence: 99%
“…Of all the above mentioned genes, CLU is the most significant gene used in combinatorial imaging analysis. The risk variant rs11136000 have been associated with reduction in hippocampal volume in patients with Late Onset Alzheimer Disease (LOAD) [80][81][82]. Apart from CLU, the risk variant rs541458 of PICALM was found to be associated with CSF Abeta 42 levels [83][84][85].…”
Section: Emerging Combinatorial Biomarkers For Admentioning
confidence: 99%